Sinergitas Kebijakan Peraturan Daerah No. 3 Tahun 2023 Tentang Penyelenggaraan Perlindungan Anak Berbasis KAS-RPA di Kota Surabaya - Fresy Widokarmeilani; Radjikan Radjikan; Muhammad Roisul Basyar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The government places the protection of women and children in Surabaya City as a top priority in efforts to reduce the annual surge of violence. To strengthen prevention, handling, and the fulfillment of women’s and children’s rights at the community level, the Surabaya City Government issued Regional Regulation No. 3 of 2023 concerning the Implementation of Child Protection, which is then implemented through the Program of Women- and Child-Friendly Arek Suroboyo Village (KAS-RPA). Focusing on Benowo District and Kandangan Subdistrict, this study aims to examine the synergy of policies among stakeholders in the implementation of the KAS-RPA program. To obtain a real understanding of the implementation conditions, this research applied a descriptive qualitative approach through field observations, in-depth interviews, and documentation. A shared perception among DP3APPKB Office, Benowo District, Kandangan Subdistrict, and Kandangan village cadres in supporting the implementation of the KAS-RPA program demonstrates the level of policy synergy achieved, according to the research findings. Communication patterns among institutions also take place openly and in a structured manner through regular coordination. The attitudes of policy actors indicate a positive commitment to the success of the program, supported by a clear and well-coordinated organizational structure. However, limitations in resources still exist, such as the lack of supporting facilities and the insufficient number of active cadres, affecting program optimization. The implications of these findings emphasize the importance of enhancing resource support and community participation to ensure a more sustainable implementation of the policy and a direct impact on reducing violence against women and children in Surabaya.